HISTOPATHOLOGICAL CHANGES OF THE MICE PLACENTA EXPOSED TO LEAD ACETATE (Iraqi Journal of Medical Sciences, 2016)
Background:Lead is one of the most dangerous metals and could be incorporated in various body tissues and thus exposure to it stills a major medical problem in both environmental and occupational setting. Objectives:To detect the deleterious and toxic effects of the lead acetate on the weight and histological features of mice placenta at different dosages.Methods: A prospective study including eighty mature pregnant mice were divided into two groups (experimental and control groups). Forty pregnant mice were divided into two major experimental groups (G1and G2) according to the level of the dose. The other forty animals with same age divided at the same way as in the previous experimental groups considered as control groups (C). Injections of lead acetate 0.1, 0.4 mg/kg body weight /day intraperitoneally (G1, G2 respectively) were started at the first day of gestation and continued for (17 or 20 days). When the female in each experimental and control groups reach day 17 of gestation 10 animals of each group were scarified, whereas the other 10 animals were left to be scarified at 20 day post coitum (dpc). Weight of placentas was recorded, in addition, histological study for these placentas were done.Results:Prenatal lead acetate injection to pregnant mice intraperitoneally for 17 day cause a significant reduction (P
Keywords: Lead; Placenta; Placental transport toxicology; Toxic trace elements; Metallothionein; Reproductive toxicology